2016
DOI: 10.1088/1361-6587/59/2/025011
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a novel type of small scale aneutronic fusion reactor

Abstract: The aim of this work is to propose a novel scheme for a small scale aneutronic fusion reactor. This new reactor type makes use of the advantages of combining laser driven plasma acceleration and electrostatic confinement fusion. An intense laser beam is used to create a lithium-proton plasma with high density, which is then collimated and focused into the centre of the fusion reaction chamber. The basic concept presented here is based on the 7 Li-proton fusion reaction. However, the physical and technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One step towards a more compact device was considered by extending the IEC device [18] with an improvement of the ion beam generation by extreme laser pulses [34]. Initially, the IEC following Hirsch used an injection of externally generated beams of ions with energies fitting good fusion reaction cross sections before working without extra ion injection and working only with the ions generated by dark ionization in the background gas due to the 50 Volts between the grid and the wall of the IEC.…”
Section: Fig 1 Cylindrical Modification Of the Inertial Electrostatic...mentioning
confidence: 99%
“…One step towards a more compact device was considered by extending the IEC device [18] with an improvement of the ion beam generation by extreme laser pulses [34]. Initially, the IEC following Hirsch used an injection of externally generated beams of ions with energies fitting good fusion reaction cross sections before working without extra ion injection and working only with the ions generated by dark ionization in the background gas due to the 50 Volts between the grid and the wall of the IEC.…”
Section: Fig 1 Cylindrical Modification Of the Inertial Electrostatic...mentioning
confidence: 99%
“…10 11 alpha particles per pulse). In recent years a new type of small-scale fusion reactor was proposed [22] along with a possible new target design [23]. The target suggested consists of alternating layers of lithium and boron with the aim of maximizing the number of fusion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the optimal shape for a solid-state proton source is a slab geometry. This paper expands on the ideas from [22,23], focusing on the optimization of the layered target. A target with three layers and four proton beams with different energy distributions are considered.…”
Section: Introductionmentioning
confidence: 99%